The Impact of Technological Innovations on Bank Performance through Accounting Data: An Applied Study on the Banking Sector (The International Journal for Scientific Research, 2026)
This study aimed to analyze the impact of technological innovations on the performance of financial companies, through a case study of the banking sector. The research was conducted on a sample of (76) employees in the banking sector, where a questionnaire was used to collect data related to technological innovations and financial performance. A set of statistical methods such as regression analysis were applied the researcher used Pearson's correlation coefficient to verify the internal consistency of the questionnaire, The results of the study showed that there is a positive impact of technological innovations on all dimensions of financial performance, including return on assets and customer satisfaction. The results also confirmed the importance of financial institutions adopting modern technologies to enhance their operational efficiency and increase their competitiveness. The study highlighted the role of innovations in improving the quality of banking service and raising productivity levels within the sector.
Keywords: Technological Innovations; Financial Performance; Banking Sector; Service Efficiency